Sex-psychological Analysis of Female Characters in Right/ Wrong Story - Pokhrel , Thakur Prasad (Adhyayan Journal, 2026)
This article, titled “Sex-psychological Analysis of Female Characters in Right/ Wrong Story,” is prepared on the basis of psychological theories. It presents the sexual desires and behavioral patterns of female characters. It shows their condition of enjoying sexual freedom according to their wishes and, at times, living separately from male friendship. The main female character, presented in narrative form, remains unmarried due to family prosperity and personal ego, and spends her life recalling past events. Her friends, Sarala and Rashmi, from their student life, live together with their lovers in the same room and complete their studies. Later, with mutual understanding, they enter married life with other young men. While remembering their behavior, the main character feels anxiety due to a lack of mental satisfaction. During her youth, because of excessive ego, she did not find a suitable partner according to her family status and personal expectations, which led her to a psychological disorder. She is portrayed as a representative of individuals affected by mental illness. Although she experiences material comforts, the incompleteness of her sexual desires results in psychological suffering. The story presents the idea that a lack of fulfillment in sexual desire leads to mental.